MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN VISUAL DALAM MATA PELAJARAN IPS KELAS IV SEKOLAH DASAR - Anggraini Saputri; Hania Dwitri Fadhia; Alfina Febrianti; Assalwa Tazkiya L; Andre Pratama Sitepu; Fatia Zulfa Nurhafifah; Muhammad Sofwan; Khoirunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe efforts to enhance students’ learning motivation through the use of visual learning media in Social Studies (IPS) subjects for fourth-grade elementary school students. The background of this research is based on the low learning motivation observed from students’ lack of active participation and enthusiasm during the learning process. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving teachers and fourth-grade students at an elementary school. The results show that the use of visual media such as images, videos, and interactive maps can attract students’ attention, facilitate understanding of the material, and increase their engagement in learning activities. Thus, visual learning media are proven to be effective in improving students’ motivation in Social Studies learning. These findings are expected to serve as a reference for teachers in selecting appropriate learning strategies to create a more enjoyable and meaningful learning process. Keywords: learning motivation, visual media, Social Studies learning, elementary school